STRATEGI PEREMPUAN DALAM KEMANDIRIAN GIZI KELUARGA (Studi Kelompok Pengajian Putri Nurul Hidayah Blabak Kota Kediri) - Handayani, Diah (IAIN Pekalongan, 2013)
Abstract : This study trying to analized the implementation of social empowerment programme as the women organization to keep the family nutrition. Nutrient balance behaviour is a knowledge, behaviour, and family about nutients in Blabak, Pesantren, Kediri. The aim of this activities is to make family able to prevent bad nutrient status and increasing nutrient status of the children. And increasing role of the women in rural areas to make the stabilization of the system by increasing the resilence of families and function empowerment and family welfare movementby the non formal organization. Also the Pengajian Nurul Hidayah strenghtening the functions and performance in order posyandu primary health care for infants and mothers. Facilitating the cooperation of the women to earn the money for providing food companion toddler feeding. Abstrak : Penelitian ini membahas tentang pelaksanaan program pemberdayaan sosial sebagai organisasi perempuan untuk menjaga gizi keluarga. Perilaku keseimbangan gizi adalah pengetahuan, perilaku, dan keluarga tentang nutrisi di Blabak, Pesantren, Kediri. Tujuan dari kegiatan adalah untuk membuat keluarga mampu mencegah status gizi buruk dan meningkatkan status gizi anak-anak, serta meningkatkan peran perempuan di daerah pedesaan untuk membuat stabilisasi sistem dengan meningkatkan pemberdayaan fungsi dan kesejahteraan keluarga oleh organisasi nonformal. Hal itu juga dilakukan oleh Pengajian Nurul Hidayah dalam penguatan fungsi dan kinerja dalam rangka pelayanan kesehatan dasar posyandu untuk bayi dan ibu. Tujuannya adalah dengan memfasilitasi kerjasama perempuan untuk mendapatkan uang untuk menyediakan pendamping makanan makan balita.